Correspondence regarding the admission of women to Cal Poly, 1954 - Julian A. McPhee:::::::::; A. A. Erhart::::::::: (1954)
A collection of three letters (that were stapled together). Written between Cal Poly President Julian A. McPhee and the California Senator for the 29th District A. A. Erhart with a copy of letter written from Senator Erhart to Dr. Roy Simpson, the State Superintendent of Public Instruction for the State Department of Education in Sacramento. The letters discuss the admission of women to Cal Poly and are dated to 1954. These letters were attached to another set of correspondence (including two copies of the letter written to Dr. Roy Simpson) and were digitized under the identifier: ua-sel_00002352